Phytochemical profile and cytotoxicity assessment of the extract from crescentia cujete l. leaves (Research, Society and Development, 2021)
Introduction: over the years, plant species have become a therapeutic alternative for a large part of the population, even with limited scientific research that ensures their effectiveness and safety. Among these, there is the Crescentia cujete, an arboreal species, with great distribution in the Northeast of Brazil. Known as the local population as a coité or gourd tree, it is used for different therapeutic purposes, such as analgesic, anti-tumor, spasmolytic and some gynecological disorders. Objective: to evaluate the possible cytotoxicity and to carry out the phytochemical characterization of the hydroalcoholic extract of Crescentia cujete. Methodology: the extract was obtained through homogenization with hydroalcoholic solution. The evaluation of cytotoxicity was based on the methodologies of erythrocyte osmotic fragility and lethality against Artemia salina L. Results: The presence of promising phytochemicals such as tannins, saponins and coumarins were detected. The cytotoxic assays showed CL50 1186.77μg / mL, considered low cytotoxic potential compared to Artemia salina L. regarding hemolytic activity, the extract obtained a percentage of 60.67%. Conclusion: therefore, it is encouraged to carry out new research in vivo and in vitro that seeks to characterize its toxic potential, as well as further studies for the quantification of phytochemicals for possible application in the development and discovery of drugs.